IDENTIFYING EXPORT OPPORTUNITIES FOR MALAYSIA USING THE SHIFT-SHARE TECHNIQUE - Mohd. Ismail Ahmad; Y. M. Mak (Asian Academy of Management Journal, 1996)
Various analytical techniques have been developed to date by researchers to identify export markets. A review of these techniques such as demand pattern analysis, income elasticity measurement, multiple factor indices, estimation by analogy, trend analysis, simple constant growth models and shift-share analysis was undertaken by Wee and Wong (1987a). There are two categories of measurements, absolute and relative. The absolute measure compares markets on a two by two basis, whereas a relative measure compares each market relative to all others in a group. The shift-share technique is a relative measure. This technique has potential for application to Malaysian exports, particularly in the current situation where a range of manufactured goods are produced and exported. In 1994 manufactured goods made up some 77 percent of Malaysian exports (Ministry of Finance, 1995) To remain viable exporters need to continually keep abreast of changing opportunities in overseas markets. This paper will illustrate the usefulness of the shift-share technique in analysing and tracking such changes in export opportunities.